Seventy Years of Life and Labor: An Autobiography of Samuel Gompers - Dick, W. M. (Labour / Le Travail, 1986)
This article reviews the book, "Seventy Years of Life and Labor: An Autobiography of Samuel Gompers," edited by Nick Salvatore.